Collective bargaining & labor relations - Herman, E. Edward; Kuhn, Alfred ;Seeber, Ronald Leroy (Englewood Cliffs, New Jersey : Prentice-Hall, 1987)
The second edition of Collective Bargaining and Labor Relations has been significantly revised and updated. The book reflects the major changes that have taken place in the labor relations arena. We have written a number of totally new chapters and sections. The field of collective bargaining and labor relations is very dynamic and in a constant state of motion. Since our first edition, there has been a major change in the industrial relations climate in the United States. Economic fluctuations, new technologies, foreign competition, a second term republican administration in Washington all had an impact on the U.S. labor scene. In the revised edition we have attempted to capture the effect of some of these changes. We have updated all our statistical material as well as our comprehensive bibliography. We also incorporated in our text recent research findings on subjects covered in this book.
Part I. Development and Growth of the Labor Moment -- Part II. The Legal Framework --Part III. The Framework of Collective Bargaining -- Part IV. Preparation for Bargaining and Costing of Labor Contracts -- Part V. The Bargaining Process: Theory, Bargaining Power, Negotiations, Impasses -- Part VI. The Content of Collective Bargaining -- Part VII. Special Topics.
Includes bibliographical references and index.
Keywords: COLLECTIVE BARGAINING